2013
DOI: 10.5194/gmd-6-2005-2013
|View full text |Cite
|
Sign up to set email alerts
|

The SPRINTARS version 3.80/4D-Var data assimilation system: development and inversion experiments based on the observing system simulation experiment framework

Abstract: Abstract. We present an aerosol data assimilation system based on a global aerosol climate model (SPRINTARSSpectral Radiation-Transport Model for Aerosol Species) and a four-dimensional variational data assimilation method (4D-Var). Its main purposes are to optimize emission estimates, improve composites, and obtain the best estimate of the radiative effects of aerosols in conjunction with observations. To reduce the huge computational cost caused by the iterative integrations in the models, we developed an of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Hakami et al (2005) and Yumimoto et al (2007Yumimoto et al ( , 2008 attempted to apply a four-dimensional variational method (a so-called advanced data assimilation method) to inverse modeling of black carbon (BC) and dust aerosols with ground-based observations and regional models. To date, measurements obtained by various observation platforms, including MODIS (Dai et al, 2014;Huneeus et al, 2012;Wang et al, 2012;Zhang et al, 2008), CALIPSO (Sekiyama et al, 2010;Zhang et al, 2011Zhang et al, , 2014, Himawari 8 (Yumimoto et al, 2016), AERONET (Schutgens et al, 2010a), and surface PM 10 (particulate matter with diameters less than 10 µm) monitoring systems (Tombette et al, 2009;Lee et al, 2013;Jiang et al, 2013), have been used in assimilation studies adopting both variational (Benedetti et al, 2009;Dubovik et al, 2008;Hakami et al, 2007;Henze et al, 2007;Yumimoto and Takemura, 2013) and ensemble-based Schutgens et al, 2010b;Di Tomaso et al, 2017;Yumimoto and Takemura, 2011) methods.…”
Section: Introductionmentioning
confidence: 99%
“…Hakami et al (2005) and Yumimoto et al (2007Yumimoto et al ( , 2008 attempted to apply a four-dimensional variational method (a so-called advanced data assimilation method) to inverse modeling of black carbon (BC) and dust aerosols with ground-based observations and regional models. To date, measurements obtained by various observation platforms, including MODIS (Dai et al, 2014;Huneeus et al, 2012;Wang et al, 2012;Zhang et al, 2008), CALIPSO (Sekiyama et al, 2010;Zhang et al, 2011Zhang et al, , 2014, Himawari 8 (Yumimoto et al, 2016), AERONET (Schutgens et al, 2010a), and surface PM 10 (particulate matter with diameters less than 10 µm) monitoring systems (Tombette et al, 2009;Lee et al, 2013;Jiang et al, 2013), have been used in assimilation studies adopting both variational (Benedetti et al, 2009;Dubovik et al, 2008;Hakami et al, 2007;Henze et al, 2007;Yumimoto and Takemura, 2013) and ensemble-based Schutgens et al, 2010b;Di Tomaso et al, 2017;Yumimoto and Takemura, 2011) methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, larger source regions show substantial fine structure and throughout the world there are also many individual sources such as in Patagonia, the Arctic plains, and countless dry or drying lake beds. Estimating dust emissions sources can also be performed with satellite data (for examples see Huneeus et al, 2012;Schutgens et al, 2012;Yumimoto and Takemura, 2013;Escribano et al, 2016Escribano et al, , 2017Di Tomaso et al, 2017). Dust models typically employ maps of dust source functions (e.g., Zender et al, 2003;Ginoux et al, 2012) because soil properties in arid and hyper-arid regions from global inventories are insufficient to provide consistent soil texture information.…”
Section: User Requirements For Desert Mineral Dust Emissionsmentioning
confidence: 99%
“…However, Fushimi et al (2011) and Chatani et al (2014) suggested that the difference in the EC concentrations between WRF-CMAQ and the measurements is largely attributed to an underestimation of the EC emission inventory, especially open biomass burning from domestic 252 D. Goto et al: Application of a global nonhydrostatic model to regional aerosol simulations around Japan sources. The local EC emission can be estimated by a combination of the data assimilation and intensive measurements (Schutgens et al, 2012;Wang et al, 2012;Yumimoto and Takemura, 2013).…”
Section: Uncertainty In the Simulationmentioning
confidence: 99%